Risk factors for postoperative complications following oral surgery - Hideo SHIGEISHI; Kouji OHTA; Masaaki TAKECHI (University of São Paulo, 2015)
AbstractObjective The objective of this study was to clarify significant risk factors for postoperative complications in the oral cavity in patients who underwent oral surgery, excluding those with oral cancer.Material and Methods This study reviewed the records of 324 patients who underwent mildly to moderately invasive oral surgery (e.g., impacted tooth extraction, cyst excision, fixation of mandibular and maxillary fractures, osteotomy, resection of a benign tumor, sinus lifting, bone grafting, removal of a sialolith, among others) under general anesthesia or intravenous sedation from 2012 to 2014 at the Department of Oral and Maxillofacial Reconstructive Surgery, Hiroshima University Hospital.Results Univariate analysis showed a statistical relationship between postoperative complications (i.e., surgical site infection, anastomotic leak) and diabetes (p=0.033), preoperative serum albumin level (p=0.009), and operation duration (p=0.0093). Furthermore, preoperative serum albumin level (<4.0 g/dL) and operation time (≥120 minutes) were found to be independent factors affecting postoperative complications in multiple logistic regression analysis results (odds ratio 3.82, p=0.0074; odds ratio 2.83, p=0.0086, respectively).Conclusion Our results indicate that a low level of albumin in serum and prolonged operation duration are important risk factors for postoperative complications occurring in the oral cavity following oral surgery.